Downside risk in reservoir management - Roseta-Palma, C.; Yiğit Sağlam (Australian Journal of Agricultural and Resource Economics, 2019)
Downside risk, which refers to deviations below a threshold, is often important in water management decisions, especially in areas with large and skewed variations in precipitation patterns. In this paper, we present a model for a reservoir manager who is downside risk averse and who performs a dynamic allocation of irrigation water, taking into account the negative effects of droughts on farm profits and different environmental constraints. We analyse the water stock, flows and agricultural profits for alternative environmental restrictions and thresholds for irrigation levels and find that stricter environmental constraints increase total water supply and carryover stock, while higher penalty thresholds lead to their overall decrease. Furthermore, increasing penalty thresholds leads to a higher emphasis on avoiding shortages, at the expense of lower average profits.